Parental exposure to the herbicide diuron results in oxidative DNA damage to germinal cells of the Pacific oyster Crassostrea gigas - Barranger, Audrey; Heude-Berthelin, Clothilde; Rouxel, Julien; Adeline, Béatrice; Benabdelmouna, Abdellah; Burgeot, Thierry; Akcha, Farida (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2016)
International audience